Day in Mamre, night in Sodom : a study of Abraham and Lot in view of the structure, language and symbolism of Genesis 18 and 19' - Letellier, Robert Ignatius (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Litt.) -- University of Stellenbosch, 1991.